Counselling and Mentoring on Human Resource Management (HR) and Operational Standards (SOP) in Pring Ledok Tinjon, Madurejo, Kec. Prambanan, Sleman District, Yogyakarta Special Region - Kusuma, Nala Tri; Cahyono, Nugroho Heri; Wibowo, Arif Ardy (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The main purpose of this abdimas activity is to provide counselling and assistance related to Human Resource Management (HR) and Operational Standards (SOP) for managers at Pring Ledok Tinjon. This abdimas activity was held at the Pring Ledok Tinjon pavilion, with 10 participants. The material presented is related to how Pring Ledok Tinjon is able to manage its human resources, improve the organisational structure, and operational standards that must be owned by a business place so that operational activities carried out can run effectively and efficiently. The material presented by the abdimas team is based on the needs and problems faced by partners. The results of the abdimas carried out are expected that the partners understand the importance of management in managing the organisation and standardisation in running operations at tourist attractions. Human Resources (HR) can be involved in the progress of Pring Ledok Tinjon, have good coordination with fellow Pring Ledok Tinjon tourism managers.